2017
DOI: 10.1111/1462-2920.13606
|View full text |Cite
|
Sign up to set email alerts
|

Abundant and rare picoeukaryotic sub‐communities present contrasting patterns in the epipelagic waters of marginal seas in the northwestern Pacific Ocean

Abstract: In this work, they compared patterns of abundant and rare picoeukaryotic sub-communities in the epipelagic waters (surface and 40-75 m depth subsurface layers) of the East and South China Seas across seasons via 454 pyrosequencing of the V4 region of 18S rDNA. They also examined the relative effects of environmental filtering, dispersal limitations and seasonality on community assembly. Their results indicated that (i) in the surface layer, abundant taxa are primarily influenced by dispersal limitations and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
107
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(142 citation statements)
references
References 74 publications
30
107
5
Order By: Relevance
“…For example, Mo et al (27) revealed that rare taxa have a stronger response to dispersal limitations than abundant bacterioplankton subcommunities in subtropical bays of China. The different result also reported by Wu et al (28), who found that abundant taxa had greater dispersal limitations in the surface layer of northwestern Pacific Ocean. (2) Abundant and rare taxa carry out different ecological strategies, may have different ecological niches, and are likely to have different responses to environmental changes.…”
Section: Introductioncontrasting
confidence: 49%
“…For example, Mo et al (27) revealed that rare taxa have a stronger response to dispersal limitations than abundant bacterioplankton subcommunities in subtropical bays of China. The different result also reported by Wu et al (28), who found that abundant taxa had greater dispersal limitations in the surface layer of northwestern Pacific Ocean. (2) Abundant and rare taxa carry out different ecological strategies, may have different ecological niches, and are likely to have different responses to environmental changes.…”
Section: Introductioncontrasting
confidence: 49%
“…In our study, dispersal significantly influenced the abundant sub‐community but not the rare sub‐community. This result is supported by a study showing that abundant taxa were more limited by dispersal than rare taxa in the surface layer of the north‐western Pacific Ocean (Wu et al ., ). Other studies have shown that rare taxa are more limited by dispersal than abundant taxa in oil‐contaminated soils (Jiao et al ., ) and subtropical bays (Mo et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…These low-abundance taxa are often referred to as the 'rare biosphere' (Sogin et al, 2006;Pedrós-Alió, 2012). The highly abundant microbes that account for the majority of microbial biomass are thought to be most important in carbon cycling (Pedrós-Alió, 2012;Wu et al, 2017). In oil-contaminated soils, abundant taxa had closer relationships with and a greater influence on the co-occurrence of other taxa than rare taxa did (Jiao et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize the chance that gene expression profiles change during sample collection, all samples were filtered immediately after they came on dock; filtration was completed within 15 min; and the filter immersed in TRIzol was immediately stored at 2208C on the ship until transport to laboratory where the samples were stored at 2808C. In addition, the sub-samples for analyzing Chl a and nutrients including phosphate, nitrate 1 nitrite, ammonia and silicate were collected and measured as previously described (Huang et al, 2010;Wu et al, 2017).…”
Section: Field Samples Collectionmentioning
confidence: 99%